1986
DOI: 10.1083/jcb.102.4.1358
|View full text |Cite
|
Sign up to set email alerts
|

A long-lived fusogenic state is induced in erythrocyte ghosts by electric pulses.

Abstract: Abstract. Treatment of erythrocyte ghosts in random positions in a suspension with membrane fusion-inducing direct current electric field pulses causes the membranes to become fusogenic. Significant fusion yields are observed if the membranes are dielectrophoretically aligned into m e m b r a n e -m e m b r a n e contact with a weak alternating electric field as much as 5 min after the application of the pulses. This demonstrates that a long-lived membrane structural alteration is involved in this fusion mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(46 citation statements)
references
References 24 publications
4
42
0
Order By: Relevance
“…The main difference between two processes is the critical voltage required for electrofusion, which is higher than for electroporation (Teissié and Rols 1993;Abidor et al 1994;Teissié and Ramos 1998), and the duration of fusogenic state, which is shorter than cell membrane resealing process. The resealing of the cell membrane after electroporation can take up to tens of minutes, while membrane fusion is only possible if the contact of permeabilized membranes is achieved within few minutes after pulse application (Teissié and Rols 1986;Sowers 1986;Ramos and Teissié 2000a). The contact needed for electrofusion can be obtained before or immediately after the electroporation pulse.…”
Section: Electrofusionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main difference between two processes is the critical voltage required for electrofusion, which is higher than for electroporation (Teissié and Rols 1993;Abidor et al 1994;Teissié and Ramos 1998), and the duration of fusogenic state, which is shorter than cell membrane resealing process. The resealing of the cell membrane after electroporation can take up to tens of minutes, while membrane fusion is only possible if the contact of permeabilized membranes is achieved within few minutes after pulse application (Teissié and Rols 1986;Sowers 1986;Ramos and Teissié 2000a). The contact needed for electrofusion can be obtained before or immediately after the electroporation pulse.…”
Section: Electrofusionmentioning
confidence: 99%
“…The contact needed for electrofusion can be obtained before or immediately after the electroporation pulse. When the cell contact is obtained before electroporation, most often dielectrophoresis is used (Zimmermann 1982), while the contact of cells after electroporation is obtained by centrifugation of fusogenic cells (Teissié and Rols 1986;Sowers 1986). …”
Section: Electrofusionmentioning
confidence: 99%
“…Cell membrane electropermeabilization must occur in order for insertion to take place. Taking into account the observation that electropermeabilization for small molecules is a long-lived process (Neumann, 1989), as is the case for the associated property of electrofusion (Sowers, 1986(Sowers, , 1987Teissi6 and Rols, 1986), we investigated the lifetime of the electroinsertioncompetent state of the membrane by adding glycophorin to previously pulsed CHO cells. An increase in bound glycophorirdcell and of labelled cells was observed even when proteins were added several minutes after cell electropulsa- tion (Fig.…”
Section: Electroinsertion Can Be An After-pulse Effectmentioning
confidence: 99%
“…In contrast, membrane fusion in erythrocyte ghosts can be delayed for several seconds or minutes after electric pulsing (Dimitrov and Sowers, 1990). This means, the electric pulses initiate a sequence of processes that, after termination of the electric field, continue to produce a long-lived fusogenic state that precedes mixing of the membranes (Sowers, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…However, for energetic reasons cells may, by the tilting of lipids, directly pass from the stalk to a modified stalk and further, by expansion of a prepore, to a fusion pore (Kuzmin et al, 2001). Moreover, earlier studies on mammalian erythrocyte ghosts (Sowers, 1986) and CHO cells (Teissié and Ramos, 1998) have indicated that cells acquire a fusogenic state that can last for minutes before they are brought into contact, this means before hemifusion of apposed membranes has an opportunity to commence (Dimitrov and Sowers, 1990). In supplementary material Movie 5, the right pair of cells appears to lack contact for 18 seconds after electric pulsing before fusion commences.…”
Section: Interpretation Of Delay Times In the Formation Of Fusion Poresmentioning
confidence: 99%